A class of max-min optimal control problems with applications to chromatography - Loxton, Ryan; Chai, Q.; Teo, Kok Lay (COC Publications, Curtin University, 2012)
In this paper, we consider a class of non-standard optimal control problems in which the objective function is in max-min form and the state variables evolve over different time horizons. Such problems arise in the control of gradient elution chromatography—an industrial process used to separate and purify multi-component chemical mixtures. We develop a computational method for solving this class of optimal control problems based on the control parameterization technique, a time-scaling transformation, and a new exact penalty method.